Occurrence of ticks in the subcutaneous tissue of red foxes, Vulpes vulpes in Czech Republic and Romania - D'Amico, G; Juránková, J; Tăbăran, F A; Frgelecová, L; Forejtek, P; Matei, I A; Ionică, A M; Hodžić, A; Modrý, D; Mihalca, A D (Ticks and tick-borne diseases, 2017)
An extensive survey of parasites in red foxes (Vulpes vulpes) was independently conducted in Romania and the Czech Republic. Carcasses were examined by necropsy, and small, dark nodules apparently containing ticks were noticed in the subcutaneous tissue of several foxes. Histopathological examination was performed using hematoxylin and eosin (HE) staining. Of the 91 foxes examined from the Czech Republic, 14 (15.4%) were harboring ticks in the subcutaneous tissue. In the majority of these cases, 1-3 nodules/fox were found, with a maximum of 31 nodules/fox. In Romania a single examined fox had subcutaneous ticks. All ticks collected from subcutaneous tissue were partially engorged adults. Based on morphological features, Ixodes ricinus, I. hexagonus, I. crenulatus and Dermacentor reticulatus were identified. The histopathological examination revealed chronic granulomatous panniculitis with peripheral fibrosis and intralesional presence of the ticks. Only few data are available regarding ticks localized in the subcutaneous tissue of any host. All the ticks were dead or already decomposed and it is evident that subcutaneous location does not represent an evolutionary advantage, as the detachment and finishing the life cycle is impossible.
Keywords: Animals; Rumunsko; Česká republika; Romania; Subcutaneous Tissue; subkutánní tkáň; zvířata; Foxes; lišky; Czech Republic; Tick Infestations; infestace klíšťaty